Emotional difficulties of university students: reflections on the contributions of socio-emotional skills training programs for students' mental health (Research, Society and Development, 2023)
The university student's routine is marked by many demands, from difficulties to emotional illness. Given this scenario, this work aims to conduct a survey on the main contributions of socio-emotional skills training programs for mental health. The method used in this study was exploratory bibliographical research that aimed to build a narrative review. For this purpose, searches were carried out for articles, theses, and dissertations indexed in the following electronic databases available online: Scientific Electronic Library Online (SciELO); Latin American and Caribbean Literature in Health Sciences (Lilacs), and Google Scholar. The following categories of descriptors were used for the research: “treinamento de habilidades socioemocionais”; “socio-emotional skills training” and “socio-emotional skills training”. All these terms were associated with the descriptor “mental health” in Portuguese, English, and Spanish. As for the results, 8 studies were found and analyzed that presented contributions of training programs for socio-emotional skills in the mental health of different sociodemographic groups. It is concluded that the use of socio-emotional skills training programs for university students can be an efficient alternative that can be adopted by higher education institutions as a way of promoting the mental health of their students and preventing illness.